Role of the Cervical Anterior Spinal Artery in the Endovascular Treatment of Vascular Diseases: Bystander, Accomplice, Victim, or Friend? - Zhang, Kun; Li, Chao; Hou, Kun; Yu, Jinlu (Frontiers in Neurology, 2021)
The cervical anterior spinal artery (ASA) is a very important artery arising from the intracranial vertebral artery (VA). It can play different roles in endovascular treatment (EVT) of spinal vascular diseases. The current understanding of these roles is incomplete; therefore, we performed this review. We found that cervical ASA can be involved in many spinal vascular diseases, such as arteriovenous fistula (AVF), arteriovenous malformation (AVM), and aneurysm, and can serve as a collateral channel in proximal VA occlusion. In AVF and AVM, when the cervical ASA is involved, it often plays the role of an accomplice or victim because it acts as the feeder or as a bystander that does not provide blood flow to the AVF and AVM. In cervical ASA aneurysm, the ASA is a victim. During EVT of VA aneurysms or stenoses, the cervical ASA ostia can be covered or occluded, resulting in ASA ischemia. In this situation, the ASA is a victim. In VA occlusion or the subclavian steal phenomenon, the cervical ASA can serve as a collateral channel to provide blood flow to the posterior circulation. In this case, the ASA plays the role of a friend. According to the role of the cervical ASA in spinal vascular diseases, EVT should be determined “case by case.” Most importantly, when EVT is performed to treat these diseases, the cervical ASA axis must be preserved. Therefore, understanding the role of the cervical ASA in spinal vascular diseases is crucial.